When violence works : postconflict violence and peace in Indonesia - Barron, Patrick, 1977- (Cornell University Press, 2019)
"Illuminates why postconflict areas so often continue to see violence and what can be done to consolidate peace in areas emerging from large-scale violent conflict"--